ESMO expert consensus statements on the screening and management of financial toxicity in patients with cancer - Carrera, Pricivel M.; Curigliano, G.; Santini, D.; Sharp, L.; Chan, R. J.; Pisu, M.; Perrone, F.; Karjalainen, S.; Numico, G.; Cherny, N.; Winkler, Eva C.; Amador, M. L.; et al. (ESMO open, 2024)
Background - Financial toxicity, defined as both the objective financial burden and subjective financial distress from a cancer diagnosis and its treatment, is a topic of interest in the assessment of the quality of life of patients with cancer and their families. Current evidence implicates financial toxicity in psychosocial, economic and other harms, leading to suboptimal cancer outcomes along the entire trajectory of diagnosis, treatment, supportive care, survivorship and palliation. This paper presents the results of a virtual consensus, based on the evidence base to date, on the screening and management of financial toxicity in patients with and beyond cancer organized by the European Society for Medical Oncology (ESMO) in 2022. - Methods - A Delphi panel of 19 experts from 11 countries was convened taking into account multidisciplinarity, diversity in health system contexts and research relevance. The international panel of experts was divided into four working groups (WGs) to address questions relating to distinct thematic areas: patients with cancer at risk of financial toxicity; management of financial toxicity during the initial phase of treatment at the hospital/ambulatory settings; financial toxicity during the continuing phase and at end of life; and financial risk protection for survivors of cancer, and in cancer recurrence. After comprehensively reviewing the literature, statements were developed by the WGs and then presented to the entire panel for further discussion and amendment, and voting. - Results and discussion - A total of 25 evidence-informed consensus statements were developed, which answer 13 questions on financial toxicity. They cover evidence summaries, practice recommendations/guiding statements and policy recommendations relevant across health systems. These consensus statements aim to provide a more comprehensive understanding of financial toxicity and guide clinicians globally in mitigating its impact, emphasizing the importance of further research, best practices and guidelines.
Online verfügbar 15 April 2024, Version des Artikels 15 April 2024
Gesehen am 27.11.2024